Back Cover: NbPt3 Intermetallic Nanoparticles: Highly Stable and CO‐Tolerant Electrocatalyst for Fuel Oxidation (ChemElectroChem 4/2014). Issue 4 (12th March 2014) - Ramesh, Gubbala V.; Kodiyath, Rajesh; Tanabe, Toyokazu; Manikandan, Maidhily; Fujita, Takeshi; Matsumoto, Futoshi; Ishihara, Shinsuke; Ueda, Shigenori; Yamashita, Yoshiyuki; Ariga, Katsuhiko; Abe, Hideki
<x xml:space="preserve">Abstract</x> The back cover artwork was chosen to show how nanoparticles of an intermetallic compound, NbPt3 (illustrated by an alchemical symbol), efficiently convert chemical energy in alcohol to electricity. NbPt3 nanoparticles catalyze the electro‐oxidation of ethanol at a lower onset potential than Pt nanoparticles. More details can be found in the Communication by Abe et al. on page 728 (DOI: 10.1002/celc.201300240).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>